The Influence of QR Code–Puzzle Towards Students’ Speaking Ability at Eight Grade of SMP Negeri 2 Kwandang - Moh. Ulfan Igirisa; Hassanudin Fatsah; Haris Danial (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study investigates the effectiveness of using QR Code - Puzzle, a puzzle combined with a QR code developed as a learning medium, in improving the English speaking ability of students at SMP Negeri 2 Kwandang. This study uses a quantitative approach with a pre-experimental design, specifically a single group design with pre- and post-tests. A total of 29 students from class VIII-4 participated in this study. The instrument used was an oral essay test consisting of 9 questions, which focused on narrative text material. After six meetings integrating QR Code puzzles with Recount Text material, the data were analyzed using the Wilcoxon Signed Rank Test with a Z value of -4.733 and Asymp. Sig. (2-tailed) .001. Since the p-value was 0.05, the null hypothesis (H₀) was rejected, and it can be concluded that there was a significant difference between the pre-test and post-test results. This shows that QR Code puzzles significantly improve students' speaking ability. These findings suggest that the integration of QR Code - Puzzle in English language learning can provide interesting, interactive, personalized, and effective support to improve speaking ability. Among the five assessed speaking components—pronunciation, grammar, vocabulary, fluency, and comprehension—comprehension showed the highest improvement, followed by pronunciation. These results suggest that the integration of QR Code–Puzzle fosters an engaging, interactive, and effective learning environment that enhances students’ overall speaking proficiency and specific linguistic competencies, particularly comprehension and pronunciation.